Roman Guardhouse at Lincoln
This is the guardhouse of the gate to the city of Lincoln. Most Roman cities were laid out on a cruciform plan with gates at four entrances to the defended rectangular enclosure, which it separated into four quarters. The plan of this building, which has an apsidal (semicircular) end, is similar to others found in Britain.